Vim master class - Cannon, Jason (Packt Publishing, 2018)
"By the time you finish Vim Masterclass, you'll know how to: Work with multiple files, including how to move data back and forth between different files, copying and pasting from one file to another, and quickly jumping to another file. You'll also learn how to view multiple files at the same time using Vim's windowing system. Use must-know keyboard shortcuts and remember them easily. You'll actually learn how to think in Vim so you don't even have to memorize each and every command, saving you countless hours of work. Find and replace entire blocks of information within a file. That includes how to refactor your code by renaming all variables in a file, or set of files, reliably. Of course, you'll learn simple find and replace techniques to replace a word in an entire file, and much more. Visually select blocks of text and edits them--for example, moving a block, deleting a block, indenting/shifting a block, and more. You'll understand Vim's text objects so you can quickly select single or multiple words, lines, paragraphs, HTML/XML tags, code blocks, and more. Make vertical edits and use Vim's Visual Block mode. (Some people call this column editing mode or rectangle mode ...). Enable syntax highlighting for source code, configuration files, or any type of file you edit often. That includes how to customize the color scheme and color code text in Vim. Employ simple-to-advanced navigation techniques so you can go to a precise location in a file very rapidly. Practical application tips such as how to edit source code, scripts, HTML, and more. You'll find lots of opportunities for practice in this course. Make the most of the built-in help system to quickly find what you need, all without leaving Vim. Use MacVim and gVim on Linux and Windows. This includes learning the advantages and disadvantages of both the textual interface and graphical Vim interfaces."--Resource description page